Comprensión lectora según género, en estudiantes del tercer y cuarto grados de educación primaria del Callao - Giraldo Ramírez, Javier Ricardo (2012)
The research aimed to establish whether there are significant differences in reading comprehension among children. The sample was made up of descriptive comparative 120 students, 33 girls and 27 third graders and 33 girls and 27 boys from the fourth grade a school of Callao. The Linguistic Complexity Progressive CLP (Alliende, Condemarín and Milicic, 1996) test was applied. adapted by (Delgado, Escurra, Atalaya, Alvarez, Small, and Guevara Santivañez (2004). The results showed that reading comprehension of third grade as the test of Mann Whitney U, show that if there are significant differences by gender in favor of girls. The fourth grade reading comprehension, as assessed by the Mann Whitney state that there are no significant differences by gender.